Ketersediaan Peralatan Listrik Bercatu Daya DC Untuk Mendukung Pemanfaatan PLTS Tanpa Inverter Pada Rumah Tangga Urban - D. Sitompul; I.N.S. Kumara; C.G.I. Partha (Jurnal SPEKTRUM, 2019)
Solar photovoltaic is one solution to provide green and sustainable electricity. Currently, most of PV application requires inverter as the electrical appliances are mostly powered by AC voltage. The inverter is the most complex components in a solar PV system as it contains complex electronic circuitry and also expensive. One solution to eliminate the use of an inverter is DC house in which power is distributed in DC voltage. For the urban consumer, which uses a wide range of electrical appliances, DC house requires the availability of DC powered electrical appliances. However, information about the availability of DC powered equipment is still limited. This paper reviews the availability of DC powered electrical appliances to get insight into the current status of this device. This study conducted an online survey targetting popular e-commerce which sells electrical appliances. The study showed that almost all electrical equipment commonly installed in the urban house of Indonesia are now available as DC powered appliances.